CD44 facilitates adhesive interactions in airineme-mediated intercellular signaling - Bowman, Raquel L.; Kim, Jiyea; Parsons, Michael J.; Eom, Dae Seok (Frontiers in Cell and Developmental Biology, 2025)
Specialized cellular protrusions facilitate local intercellular communication in various species, including mammals. Among these, airinemes play a crucial role in pigment pattern formation in zebrafish by mediating long-distance Notch signaling between pigment cells. Remarkably, airinemes exhibit large vesicle-like structures at their tips, which are pulled by macrophages and delivered to target cells. The interaction between macrophages and Delta-ligand-carrying airineme vesicles is essential for initiating airineme-mediated signaling, yet the molecular details of this interaction remain elusive. Through high-resolution live imaging, genetic in vivo manipulations, and in vitro adhesion assays, we found that adhesive interactions via the extracellular domain of CD44, a class I transmembrane glycoprotein, between macrophages and airineme vesicles are critical for airineme signaling. Mutants lacking the extracellular domain of CD44 lose their adhesiveness, resulting in a significant reduction in airineme extension and pigment pattern defects. Our findings provide valuable insights into the role of adhesive interactions between signal-sending cells and macrophages in long-range intercellular signaling.